Information transmission and countervailing biases in organizations - Saori Chiba (Games, 2024)
A decision maker (DM) must choose between two projects or decide on no project. The expected benefits of these projects are correlated. The DM seeks advice from an agent with private information about the projects' benefits. However, the agent's divergent preferences for projects and lack of consideration for the DM's implementation costs may introduce two types of biases: project bias, favoring the agent's project, or pandering bias, favoring the project preferred by the DM. Our findings reveal that project correlation leads to these biases countervailing each other, facilitating the transmission of information. The agent typically recommends a project based on private information to dissuade the DM from choosing no project, as this would be detrimental to the agent. Additionally, we explore optimal delegation within organizations. In contrast to the prevailing literature advocating for delegation to biased agents for enhanced information elicitation, our study suggests limited benefits in the context of project correlation.
Keywords: C72; D23; D83; 330; bias; cheap talk; correlation; outside options